Neuropharmacological basis for multimodal analgesia in chronic pain. Issue 3 (3rd April 2022) - Patel, Ryan; Dickenson, Anthony H
ABSTRACT: Managing chronic pain remains a major unmet clinical challenge. Patients can be treated with a range of interventions, but pharmacotherapy is the most common. These include opioids, antidepressants, calcium channel modulators, sodium channel blockers, and nonsteroidal anti-inflammatory drugs. Many of these drugs target a particular mechanism; however, chronic pain in many diseases is multifactorial and induces plasticity throughout the sensory neuroaxis. Furthermore, comorbidities such as depression, anxiety, and sleep disturbances worsen quality of life. Given the complexity of mechanisms and symptoms in patients, it is unsurprising that many fail to achieve adequate pain relief from a single agent. The efforts to develop novel drug classes with better efficacy have not always proved successful; a multimodal or combination approach to analgesia is an important strategy in pain control. Many patients frequently take more than one medication, but high-quality evidence to support various combinations is often sparse. Ideally, combining drugs would produce synergistic action to maximize analgesia and reduce side effects, although sub-additive and additive analgesia is still advantageous if additive side-effects can be avoided. In this review, we discuss pain mechanisms, drug actions, and the rationale for mechanism-led treatment selection. Abbreviations : COX – cyclooxygenase, CGRP – calcitonin gene-related peptide, CPM – conditioned pain modulation, NGF – nerve growth factor, NNT – number needed to treat, NMDA – N -methyl-d -aspartate, NSAID – nonsteroidal anti-inflammatory drugs, TCA – tricyclic antidepressant, SNRI – serotonin-noradrenaline reuptake inhibitor, QST – quantitative sensory testing.